Influence of recycled HDPE as partial coarse aggregate replacement on permanent deformation of modified asphalt mixture - Wan Rohaya, Wan Idris (2010)
Rutting or permanent deformation is one of the asphalt pavement failures due to stresses caused by the traffic load pressures. This permanent deformation cause rutting failure of structure. This study was done in effort to produce durable and long service life of asphalt pavement by modify, the asphalt with waste HDPE. The study on modification of asphalt mixture was proposed to evaluate the effect of using HDPE in pallet form as coarse aggregate replacement on 80/100 grade penetration of bitumen and also to develop optimum quality of modified asphalt mixture content H1)PE as aggregate replacement. The HDPE was used to replace coarse aggregate size between 3.3 5mm until 14mm. Bitumen content used for control specimens was in range between 4%-6%. The aggregate was replaced by HDPE pallets between 10% until 50%. From the individual graph of void, bulk density, and resilient modulus versus bitumen content, the averaged optimum bitumen content (OBC) for control asphalt mix obtained was 4.7%. This OBC value was used to produce modified specimen with waste HDPE. Three modified samples were produce for each percent of HDPE replacement. A 20 1/o coarse aggregate replacement by volume results in reduction in bulk density of 13.6%. Modified asphalt was affected by temperature which is the reduction of resilient modulus value at 20°C and 40°C was 82.5%. HDPE was found can increase the ability of asphalt mix to resist permanent if the appropriate percent of HDPE content use. In conclusion, at optimum bitumen content 4.7% and optimum HDPE content 20%, the modified asphalt mixture produce the optimum performance in form of permanent deformation behavior with the lowest strain value.